Theoretical Determination of Corrosion Inhibitor Activities of Naphthalene and Tetralin - Omer, Rebaz Anwar; Koparir, Pelin; Qader, Ibrahim Nazem; Ahmed, Lana Omer (Gazi Univ, 2022)
Quantum mechanical methods were used to investigate the corrosion inhibitor activities of tetraline and naphthalene compounds. In this study, some parameters were estimated, including, the energy of the highest occupied molecular orbital (E-HOMO), the energy of the lowest occupied molecular orbital (E-LUMO), the energy bandgap (Delta E = E-LUMO - E-HOMO), and the dipole moment (mu). The aforementioned parameters give information about the corrosion efficiency of organic compounds. Furthermore, the density functional theory (DFT) was handled to determine the geometry of the molecules and electronic characteristics of the compounds. B3LYP/6-31G (d, p) was utilized to determine physical parameters such as hardness (eta), softness (sigma), and electronegativity (chi). We also evaluated quantum chemistry characteristics including the fraction of electrons transported (Delta N) between the iron surface and our title compounds. This study also discusses which parameters have a significant linear relationship with inhibitory performance. The findings suggest that the behavior of organic-based corrosion inhibitors is correlated with the effectiveness of good corrosion inhibitors and the quantum chemical parameters measured from this process. As a result, the behavior of corrosion inhibitors can be determined without the need for an experiment.
Keywords: Naphthalene; Tetralin; DFT; Inhibitor activity